PENELITIAN EFISIENSI PUMP AS TURBINE (PAT) UNTUK MENDUKUNG PERENCANAAN DAN IMPLEMENTASI PLTMh DI KABUPATEN SUMBAWA - Alfian Rusdi; Agus Maryono; Suhanan - (ASEAN Journal of Systems Engineering, 2014)
The energy crisis will come soon, the consumption behavior and economic elevating will advance the energy depletion. The demand of power electrical around 4.000 – 5.000 MW per year will difficult to fix, if we just rely on fossil energy because of the increasing oil world price. The water energy is one of the renewable energy can be used as solution. Based on annual reporting of PT PLN (Persero) area NTB in 2012. Province of  NTB has hydropower potential 82,35 MW but until 2012 the ratio electrical is 50,95%. The building of PLTA need high cost, so PLTMh is considered to solve soon the village electrical demand.Dusun Kaduk in Kabupaten Sumbawa Province of NTB is one of the hilly and purilieus village area that has potential of coffee field, but doesn’t has electrical sources. Pump as Turbine (PaT) is designed to change generator. The advance of PaT are easy instalation and maintanance, mass production, avalaible spare part and low investation so can utilize the maximum water potential. The purpose of research to examine the suit PaT for local area, to analize capability the centrifugal water pump type semi-open impeller SU-50 be used as PaT and to get the characteristic of relation between water discharge to output power. The experimental method is used to examine the layout PaT directly and note the parameters used to analize of data.The result of the research show the the centrifugal water pump type semi-open impeller SU-50 used as PaT can produce 911,73 rpm, The maximum power 61,09 W at head 4 m and the highest efficiency 19,05 %. The modified impeller by using forward blade close impeller can increase 935 rpm, the maximum power 62,35 W at head 4 m and the highest efficiency 20,42 %. The highest spin 1194,83 rpm, the maximum power 85,80 W at head 4 m with efficiency until 34,79 % is got by using backward blade close impeller. Result of similarity analysis if discharge 85 l/s, head 21 m, diameter of pump 0,523 m and highest spin 1600,094 rpm can produce power 311,211 kW. Based the research  the PaT can be used as alternative of electrical power sources in village.